Flypaper Effect Pada Pendapatan Asli Desa, Dana Desa, dan Alokasi Dana Desa Terhadap Belanja Desa di Kabupaten Kudus - Ulya, Fatikhatuddirosatin Nuril; Rakhmawati, Ita (AKTSAR: Jurnal Akuntansi Syariah, 2024)
Village expenditures are all from the village's general cash account which reduces the excess budget balance in the period of the relevant fiscal year for which the village government will not receive repayment. This research aims to empirically prove the influence of PADes, village funds, and village fund allocation on village spending and to prove whether the phenomenon exists or not. flypaper effect from transfer funds. This research is descriptive research with a quantitative approach. The research sample consisted of 121 villages obtained through the purposive sampling technique during the 2019–2022 period. The research data is secondary data obtained from the realization report of the Kudus Regency village income and expenditure budget. The variables in this research consist of independent variables including PADes, DD, and ADD, while the dependent variable is village expenditure. This research uses panel data regression analysis tools with the selected random effect model, which was processed with the help of Eviews 12. The research results show that village original income, village funds, and village fund allocation have a significant positive effect on village expenditure. As many as 46% of villages were proven to experience the phenomenon of the flypaper effect because the original income obtained was smaller than village funds and village fund allocations. This shows the high dependence of the village on external funding.